Innovation in Waqf Management: Integrating Risk Management in a Sustainable Business - Vernon, Annisa Della (ICO EDUSHA, 2024)
Waqf management as a social financial instrument has a very important role in community economic development and social sustainability. However, its management is often hampered by a lack of understanding of the importance of risk management in maintaining its sustainability and effectiveness. This study aims to examine how innovations in waqf management can be made by integrating risk management in a sustainable business plan. Through a qualitative approach, this study identifies and analyzes risk factors that can affect the success of waqf management as well as mitigation strategies that can be applied in waqf management. The results of this study are expected to contribute to the improvement of the quality of waqf management and provide practical recommendations to increase the social and economic impact of waqf. Keywords: Waqf Management, Risk Management, Business Plan